PERAN E-PEKEN DALAM PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) UNTUK MEWUJUDKAN LESS CASH SOCIETY - Suwardianto, Rico Adi (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the effect of E-peken on the development of MSMEs, explain its impact on Less Cash Society, and test how E-peken affects MSMEs towards Less Cash Society. The method is quantitative research with the use of Likert scale in the questionnaire. Data was obtained from online shopping consumers through E-peken in MSMEs in Genteng Subdistrict, Surabaya City, with a sample of 30. Data analysis used the component-based SEM method with PLS as an analytical tool. The results of the analysis show that the application of E-peken is proven to have a significant positive effect on MSME Development, with a t-statistic value that exceeds the t-table value and a p-value that is smaller than the significance level Î± = 0.05, indicating that the higher the application of E-peken, the higher the development of MSMEs. Secondly, the reputation of E-peken is also shown to have a significant positive effect on Less Cash Society, characterized by a t-statistic value that far exceeds the t-table and a very low p-value, confirming that a good reputation of E-peken encourages higher adoption of the Less Cash Society concept by employees. In addition, the R-Square evaluation confirms that the E-peken variable substantially explains the variation in MSME Development (59.0%) and Less Cash Society (46.8%), emphasizing the crucial role of E-peken in promoting MSME growth and reducing the use of cash in society.